Synopsis: Non-farm income and labor markets in rural Ethiopia - Bachewe, Fantu Nisrane; Berhane, Guush; Minten, Bart; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2016)
Ethiopia’s economy is rapidly transforming. However, the extent to which this is affecting off-farm income and labor markets in rural areas is not well understood. Based on a large-scale household survey in high potential agricultural areas of the country, we find that total off-farm income (defined as wage and enterprise income) makes up 18 percent of total rural income. Wage income in both the agricultural and non-agricultural sectors accounts for 10 percent of total household income, equating in importance to livestock income. We show off-farm income and wage income to be relatively more important for the poor and for female and youth-headed households. We further find that real rural wages increased by 54 percent over the last decade, mostly driven by high agricultural growth. While this wage increase is good news for the poor, it also induces adjustments in agricultural production practices, including increased adoption of labor-substituting technologies, such as herbicides.